2020
DOI: 10.1101/2020.03.03.20030650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunodepletion with Hypoxemia: A Potential High Risk Subtype of Coronavirus Disease 2019

Abstract: Background The outbreak of COVID-2019 is becoming a global public health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 10 publications
1
62
0
3
Order By: Relevance
“…The infectious form of the virus was even identified several times, suggesting that the orofecal route is a mode of contamination (1). The gut involvement might explain the wide variation in viral load from one test to another in the same person as if the virus were hiding there (2). Chinese researchers have investigated changes in the microbiota in the patients who have died for COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…The infectious form of the virus was even identified several times, suggesting that the orofecal route is a mode of contamination (1). The gut involvement might explain the wide variation in viral load from one test to another in the same person as if the virus were hiding there (2). Chinese researchers have investigated changes in the microbiota in the patients who have died for COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…The elevated IL-6 was significantly related to the clinical manifestation of severe type patients [34]. An analysis of dynamic characteristics of host immune system in 3 critical cases showed that hypoxemia severity was closely related with host immune cell levels [35], and the lymphocytopenia and cytotoxicity may be the result of SARS-CoV-2 infection [36]. An observation showed that after SARS-CoV-2 infection, CD4 + T lymphocytes are rapidly activated to become pathogenic T helper (Th) 1 cells and generate cytokines including GM-CSF.…”
Section: Pathogenesis Of Cytokine Release Syndrome Induced By Sars-cov-2mentioning
confidence: 92%
“…One can speculate that the decrease in ACE2 availability during SARS-COV-2 infection is enough to alter the composition of the gut microbiota. Recent pilot studies suggest gut microbiota alterations during SARS-CoV-2 infection (Yu et al, 2020;Gu et al, 2020b;Zuo et al, 2020). In a cohort of 30 COVID-19 patients (fecal sample analysis using 16S rRNA gene sequencing), infection was associated with a significant decrease of bacterial diversity and abundance (Gu et al, 2020b).…”
Section: Ace2 Dysfunction Alters the Composition Of The Gut Microbiotamentioning
confidence: 99%